2022
DOI: 10.1093/ornithapp/duac003
|View full text |Cite
|
Sign up to set email alerts
|

Automated bird sound classifications of long-duration recordings produce occupancy model outputs similar to manually annotated data

Abstract: Occupancy modeling is used to evaluate avian distributions and habitat associations, yet it typically requires extensive survey effort because a minimum of 3 repeat samples are required for accurate parameter estimation. Autonomous recording units (ARUs) can reduce the need for surveyors on-site, yet their utility was limited by hardware costs and the time required to manually annotate recordings. Software that identifies bird vocalizations may reduce the expert time needed if classification is sufficiently ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 36 publications
3
34
0
Order By: Relevance
“…However, the recall rate obtained using BirdNET is among the highest values ever published using this technique. For example, Cole et al (2022) recently evaluated BirdNET for detecting 13 bird species in North America and found that the recall rate ranged from 9% to 68%. Similarly, the recall rate obtained by Tolkova et al (2021) ranged between 11% and 71% for three common bird species.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the recall rate obtained using BirdNET is among the highest values ever published using this technique. For example, Cole et al (2022) recently evaluated BirdNET for detecting 13 bird species in North America and found that the recall rate ranged from 9% to 68%. Similarly, the recall rate obtained by Tolkova et al (2021) ranged between 11% and 71% for three common bird species.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the state-of-the-art techniques for handling big datasets, such as deep learning and convolutional neural networks (Stowell, 2022;Stowell et al, 2019), can be difficult to run for ornithologists, managers, and researchers without bioacoustics or engineering backgrounds. However, user-friendly and ready-to-use machine learning approaches have recently been developed and are increasingly accessible to respond to real-life monitoring challenges and the general public (Cole et al, 2022). Among these approaches is Bird-NET, a research project between The Cornell Lab of Ornithology and the Chemnitz University of Technology.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to choosing the confidence score threshold, BirdNET also allows users to adjust the overlap of prediction segments (overlapping segments will increase the detection resolution but also the processing time; Kahl et al 2021) and the sensitivity parameter (higher values may work better in speciesrich soundscapes; Kahl et al 2021), as well as to apply spatial and temporal filters (e.g. classify sounds only for species on eBird checklists for a certain location and/or period; Cole et al 2022) or specify a custom list to classify sounds only for target species (see Manzano et al 2022).…”
mentioning
confidence: 99%
“…Indeed, several recent studies have employed BirdNET automatically to classify bird vocalizations and draw ecological or conservation inferences from the data collected (e.g. Cole et al 2022, Wood et al 2022. Bird-NET precision (% detections correctly classified) was claimed to be about 0.8-0.9 in focal recordings (Arif et al 2020 but it seems to decrease considerably for sound recordings collected using omnidirectional microphones (Wood et al 2021).…”
mentioning
confidence: 99%